The Influence of Institutional Ownership and the Proportion of the Independent Board of Commissioners on Tax Avoidance with Moderation Size for the 2019-2021 Period - Safira, Dea Natalia; Jaunanda, Meiliana (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
This study discuss the effect of Institutional Ownership and Proportion of Independent Commissioners by using size as the moderating variable. The Independent variables in this study are Institutional Ownership and The Proportion of Independent Commissioners, the moderating variable is Size or company size, and the control variables are Gross Profit Margin, Return on Sales, and Debt-to-Equity Ratio. This study uses secondary data from manufacturing companies listed on the IDX for the period 2019-2021. The result of this study prove that Institutional Ownership has a negative and significant effect on Tax Avoidance (1), the proportion of the Board of Commissioners has a significant positive effect on Tax Avoidance (2), Size strengthens the relationship between Institutional Ownership and Tax Avoidance (3), Size weakens the relationship between Proportion of Independence Commissioners on Tax Avoidance (4).